The most common reasons for health encounters in a community assisted by a health team in Fortaleza, Ceará - Santos, Karina de Paula Bastos (2015)
Objective: the aim of this study was to establish the main reasons for engaging in consultations with a health team in Fortaleza, Ceará. Methods: the data were collected from medical records covering the first semester of 2012. They were extracted from a secondary database, coded using ICPC, and then entered into an Excel spreadsheet. Results: there were 1,044 different encounters recorded, 68% with female patients and 32% with males. Most of the patients were between 20 and 39 years old. There were 1,985 reasons for encounters, the most common of which were categorized as General and Unspecified, Respiratory, Digestive, Musculoskeletal, and Cardiovascular. The main 30 reasons for encounters accounted for 51.49% of the total number. People raised a great number of demands, most of which related to the program. Conclusion: the ICPC2 program helped to precisely evaluate patients’ demands. Therefore, this study showed that the program was a tool by which the health team could take care of people through capacitation, managing the clinic, and developing actions for the individuals and community to face issues that arise ive, Musculoskeletal, and Cardiovascular. The main 30 reasons for encounters accounted for 51.49% of the total number. People raised a great number of demands, most of which related to the program. Conclusion: the ICPC2 program helped to precisely evaluate patients’ demands. Therefore, this study showed that the program was a tool by which the health team could take care of people through capacitation, managing the clinic, and developing actions for the individuals and community to face issues that arise.